Cross-sectional survey on bronchoscopy in Germany: the current status of clinical practice - Hautmann, Hubert; Hetzel, J.; Eberhardt, Ralf; Stanzel, F.; Wagner, M.; Schneider, A.; Dirschinger, R.; Poszler, A. (Pneumologie, 2016)
Objectives: Bronchoscopy is an integral part of pulmonary medicine. In recent years, a series of new technologies have evolved. It is to assume that significant changes have also occurred in clinical practice. We conducted a nationwide survey to evaluate the current status of care and to compare it with earlier reports. Methods: A standard questionnaire was sent to 1875 institutions to assess the clinical practice of bronchoscopy in Germany with respect to general issues, education, sedation/anaesthesia and technical aspects. Results: The returned questionnaires cover 301,965 bronchoscopies, performed by 2158 physicians over 12 months, making it the largest survey to date. The proportion of rigid bronchoscopies has decreased and amounts to 7.3 % at present. Atropine as a premedication is hardly used any more. Sedation is routinely applied in 88 % of flexible bronchoscopies, for which a combination of propofol and midazolam is preferred by most institutions (41.3 %), followed by propofol monotherapy (28.3 %). 74.4 % of institutions accept aspirin for transbronchial biopsy, 8.1 % dual platelet inhibition. 62.4 % of all institutions perform airway recanalisation, favouring cryotherapy and argon plasma coagulation. 9.1 % of bronchoscopies are supported by endobronchial ultrasound. Conclusion: Compared to preceding surveys, the experience of bronchoscopists, especially regarding interventional procedures, has increased. Endobronchial ultrasound has become a standard of care, as has patient sedation with propofol.
Gesehen am 07.05.2020